2022
DOI: 10.3390/plants11121602
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Regulation of Ascorbic Acid in Fruits

Abstract: Ascorbic acid, also known as vitamin C, is a vital antioxidant widely found in plants. Plant fruits are rich in ascorbic acid and are the primary source of human intake of ascorbic acid. Ascorbic acid affects fruit ripening and stress resistance and plays an essential regulatory role in fruit development and postharvest storage. The ascorbic acid metabolic pathway in plants has been extensively studied. Ascorbic acid accumulation in fruits can be effectively regulated by genetic engineering technology. The acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 156 publications
0
15
0
Order By: Relevance
“…l -Ascorbic acid (vitamin C) is one of the primary hydrosoluble antioxidants of the fruit and is an essential component of human nutrition ( Zheng et al, 2022 ). A previous study revealed that LAB fermentation could protect l -ascorbic acid from oxidation, thereby retaining the freshness of fruits and vegetables ( Bergqvist et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…l -Ascorbic acid (vitamin C) is one of the primary hydrosoluble antioxidants of the fruit and is an essential component of human nutrition ( Zheng et al, 2022 ). A previous study revealed that LAB fermentation could protect l -ascorbic acid from oxidation, thereby retaining the freshness of fruits and vegetables ( Bergqvist et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…The increase of the citric acid content in the LRFCJ samples may be ascribed to the hydrolytic activity of the microorganism, which can induce the higher release of citric acid from sweet cherry juice (Delgado-Ospina et al, 2020). l-Ascorbic acid (vitamin C) is one of the primary hydrosoluble antioxidants of the fruit and is an essential component of human nutrition (Zheng et al, 2022). A previous study revealed that LAB fermentation could protect l-ascorbic acid from oxidation, thereby retaining the freshness of fruits and vegetables (Bergqvist et al, 2005).…”
Section: Characterization Of the Organic Acids Profilementioning
confidence: 99%
“…In addition, fungi species are known to synthesize VC analogs, such as D-erythroascorbate [ 102 ]. Due to the comprehensive reviews on the subject [ 17 , 68 , 80 , 94 , 103 ], and lack of significant recent advances, these will be only briefly discussed to highlight the main differences between pathways.…”
Section: Vitamin C Biosynthetic Pathways: the Current Statusmentioning
confidence: 99%
“…In plants, VC plays an active role on overall stress perception and response [ 65 , 66 , 67 , 68 ]. Indeed, VC has been shown to ameliorate the negative effects of high salinity and heavy metal exposure in agricultural crops [ 67 , 69 , 70 , 71 , 72 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the genes PAL ( phenylalanine-ammonia-lyase ), C4H ( cinnamate 4-hydroxylase ), 4CL ( 4-coumarate-CoA ligase ), CHS ( chalcone synthase ), HCT ( hydroxycinnamoyl-CoA shikimate ), HQT ( hydroxycinnamoyl-CoA quinate ) and transcriptions factors (TFs) as MYB and basic helixloop-helix (bHLH) play a role in the regulation of the synthesis of these compounds ( Vogt, 2010 ; Valiñas et al., 2015 ; Valcarcel et al., 2016 ). On the other hand, the ascorbic acid is synthesized at least by four pathways, the L-Galactose ( Wheeler et al., 1998 ; Wheeler et al., 2003 ), the L-Glucose ( Wheeler et al., 2003 ; Wolucka and Van Montagu, 2003 ), the D-Galacturonate ( Agius et al., 2003 ; Wheeler et al., 2003 ), and the Myo-Inositol pathways ( Lorence et al., 2004 ); where genes as DHA ( ascorbate peroxidase ), GDH ( D-galacturonate reductase ), GGP ( L-galactose dehydrogenase ), GME ( L-galactono-1,4-lactone dehydrogenase ), GMP ( GDP-D-mannose3′, 5′-epimerase ) among others have a role in the synthesis of this component ( Caruso et al., 2021 ; Zheng et al., 2022 ). Yet, reports about the genes associated with ascorbic acid synthesis and its antioxidant activity in potatoes are not available.…”
Section: Introductionmentioning
confidence: 99%